2017
DOI: 10.1016/j.bmcl.2017.05.022
|View full text |Cite
|
Sign up to set email alerts
|

Antiviral escin derivatives from the seeds of Aesculus turbinata Blume (Japanese horse chestnut)

Abstract: Porcine epidemic diarrhea virus (PEDV) causes severe diarrhea and high fatality of piglets, influencing the swine industry. Japanese horse chestnut (seed of Aesculus turbinata) contains many saponin mixtures, called escins, and has been used for a long time as a traditional medicinal plant. Structure-activity relationship (SAR) studies on escins have revealed that acylations at C-21 and C-22 with angeloyl or tigloyl groups were important for their cytotoxic effects. However, the strong cytotoxicity of escins m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
24
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(24 citation statements)
references
References 31 publications
(13 reference statements)
0
24
0
Order By: Relevance
“…Usually, a more efficient or safer drug can be designed based on the original natural compound that exhibits the wanted activity. Kim et al (2017) designed and synthesized a series of escin derivatives without the angeloyl or tigloyl groups that are important for cytotoxicity of escins and modified glycosidic linkages by hydrolysis. Those Escin derivative showed lower cytotoxicity.…”
Section: Natural Products Inhibiting Sars-covmentioning
confidence: 99%
“…Usually, a more efficient or safer drug can be designed based on the original natural compound that exhibits the wanted activity. Kim et al (2017) designed and synthesized a series of escin derivatives without the angeloyl or tigloyl groups that are important for cytotoxicity of escins and modified glycosidic linkages by hydrolysis. Those Escin derivative showed lower cytotoxicity.…”
Section: Natural Products Inhibiting Sars-covmentioning
confidence: 99%
“…154 It also has anticancer activity through intrinsic-mitochondrial apoptosis pathway by arresting G2/M and ROS generation. 155 The antiviral activity of escin has been reported against porcine epidemic diarrhea virus (PEDV), 156 HIV-1 157 and SARS-CoV. 158 Strong cytotoxicity of escins create a challenge for their drug development.…”
Section: Escinmentioning
confidence: 99%
“…159 However, SAR studies have shown that acylations at C-21 and C-22 with angeloyl or tigloyl groups were important for their cytotoxic effects. 156 Thus, escin derivatives with strong antiviral activities have been reported. 156 Moreover, it is an approved, well tolerated anti-edematous, anti-inflammatory drug.…”
Section: Escinmentioning
confidence: 99%
See 1 more Smart Citation
“…chekiangensis (Hu et Fang) Fang obtained various types of isolates, for example, triterpenoids (Yuan et al, 2013), flavonoids (Kapusta et al, 2007), coumarins (Niu et al, 2015) together with steroids (Zhang et al, 2009). Polyhydroxylated triterpenoid saponins, isolated from Aesculus genus (Wei et al, 2004;Kim et al, 2017) with great structural diversity, have been proved to be the major bioactive principles including anticancer (Patlolla et al, 2006), neuroprotective (Cheng et al, 2016), anti-inflammatory (Matsuda et al, 1997), antioxidative (Küçükkurt et al, 2010), and antiedematous activities (Piller, 1976). As part of our continuous research to screen cytotoxic and neuroprotective compounds of this type, a series of new triterpenoids (1-14) along with 19 reported analogs (15-33) from the seeds of Aesculus chinensis Bge.…”
Section: Introductionmentioning
confidence: 99%